2014
DOI: 10.1155/2014/640406
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Pattern Recognition in Electrofacies Analysis

Abstract: Pattern recognition is an important analytical tool in electrofacies analysis. In this paper, we study several commonly used clustering and classification algorithms. On the basis of advantages and disadvantages of existing algorithms, we introduce the KMRIC algorithm, which improves initial centers ofK-means. Also, we propose the AKM algorithm which automatically determines the number of clusters and apply support vector machine to classification. Finally, we apply these algorithms to electrofacies analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It also represents the target of electrofacies classification and the way in where the final categorization will be interpreted and used. In our experiment, we selected five electrofacies classes to be constructed by a non hierarchical k-means clustering algorithm, which is one of the most popular and widespread partitioning clustering algorithms because of its superior feasibility and efficiency in dealing with a large amount of data [39]. Several studies have suggested and used k-means clustering for constructing electrofacies [18,27].…”
Section: Clustering the Logsmentioning
confidence: 99%
“…It also represents the target of electrofacies classification and the way in where the final categorization will be interpreted and used. In our experiment, we selected five electrofacies classes to be constructed by a non hierarchical k-means clustering algorithm, which is one of the most popular and widespread partitioning clustering algorithms because of its superior feasibility and efficiency in dealing with a large amount of data [39]. Several studies have suggested and used k-means clustering for constructing electrofacies [18,27].…”
Section: Clustering the Logsmentioning
confidence: 99%